2017
DOI: 10.17344/acsi.2017.3295
|View full text |Cite
|
Sign up to set email alerts
|

N,N,N’,N’-Tetrabutyl-1,10-phenanthroline- 2,9-dicarboxamide as Very Effective Extraction Agent for Trivalent Europium and Americium

Abstract: Solvent extraction of microamounts of Eu 3+ and Am 3+ from water into nitrobenzene by means of a mixture of hydrogen dicarbollylcobaltate (H + B -) and N,N,N',N'-tetrabutyl-1,10-phenanthroline-2,9-dicarboxamide (L) N,N,N',N'-tetrabutyl-1,10-phenanthroline-2,9-dicarboxamide) are extracted into the nitrobenzene phase. Extraction and stability constants of the cationic complex species in nitrobenzene saturated with water were determined and discussed. From the experimental results it is evident that this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Being of enough complexation strength to actinides of various valences as well as high actinide selectivity over lanthanides, mixed N- and O-donor ligands are potential separation reagents for the GANEX process. Diamide derivatives of bipyridinedicarboxylate (BiPDA) and phenanthrolinedicarboxylate (PhenDA) are the most intensively investigated mixed N- and O-donor ligands. N , N ′-Diethyl- N , N ′-phenyl-2,2′-bipyridine-6,6′-dicarboxamide, synergistic by the lipophilic anion source chlorinated cobalt dicarbollide in fluorinate diluents, was found to be selective to extract Am from lanthanides ( SF Am/Eu ≤ 30). , N , N ′-Diethyl- N , N ′-ditolyl-2,9-diamide-1,10-phenanthroline exhibited excellent extraction ability and high selectivity toward hexavalent ( SF U/Eu ≤ 277), tetravalent ( SF Th/Eu ≤ 2277), and trivalent ( SF Am/Eu ≤ 67) actinides over lanthanides in high acidic solution (1.0 M HNO 3 ), using cyclohexanone as diluent. , The highly preorganized mixed N- and O-donor ligand like unsaturate δ-lactam-1,10-phenanthroline (BLPhen) effectively extracted Am­(III) from 3 M HNO 3 solution into dichloroethane with high selectivity for Am­(III) over Eu­(III) ( SF Am/Eu ≤ 211) . It is well-known that the complexation between ligand and metal ion is the chemical basis behind separation in liquid extraction, but limited studies on the complexation of such tetradentate N-O-O-N ligands with lanthanides/actinides in a homogeneous phase and the complex structures in solid have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being of enough complexation strength to actinides of various valences as well as high actinide selectivity over lanthanides, mixed N- and O-donor ligands are potential separation reagents for the GANEX process. Diamide derivatives of bipyridinedicarboxylate (BiPDA) and phenanthrolinedicarboxylate (PhenDA) are the most intensively investigated mixed N- and O-donor ligands. N , N ′-Diethyl- N , N ′-phenyl-2,2′-bipyridine-6,6′-dicarboxamide, synergistic by the lipophilic anion source chlorinated cobalt dicarbollide in fluorinate diluents, was found to be selective to extract Am from lanthanides ( SF Am/Eu ≤ 30). , N , N ′-Diethyl- N , N ′-ditolyl-2,9-diamide-1,10-phenanthroline exhibited excellent extraction ability and high selectivity toward hexavalent ( SF U/Eu ≤ 277), tetravalent ( SF Th/Eu ≤ 2277), and trivalent ( SF Am/Eu ≤ 67) actinides over lanthanides in high acidic solution (1.0 M HNO 3 ), using cyclohexanone as diluent. , The highly preorganized mixed N- and O-donor ligand like unsaturate δ-lactam-1,10-phenanthroline (BLPhen) effectively extracted Am­(III) from 3 M HNO 3 solution into dichloroethane with high selectivity for Am­(III) over Eu­(III) ( SF Am/Eu ≤ 211) . It is well-known that the complexation between ligand and metal ion is the chemical basis behind separation in liquid extraction, but limited studies on the complexation of such tetradentate N-O-O-N ligands with lanthanides/actinides in a homogeneous phase and the complex structures in solid have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that the complexation between ligand and metal ion is the chemical basis behind separation in liquid extraction, but limited studies on the complexation of such tetradentate N-O-O-N ligands with lanthanides/actinides in a homogeneous phase and the complex structures in solid have been reported. Borisova and co-workers found that the affinity of different 2,2′-bipyridyl-6,6′-dicarboxamide ligands to lanthanides decreased linearly with increasing atomic number of the lanthanide, and Hancock and co-workers observed that the affinity of 1,10-phenanthroline-2,9-dicarboxamide to lanthanides had a similar but unobvious trend. , However, Hancock and co-workers determined some 1:1 lanthanide and actinide complexes with PhenDA, but did not find a similar trend for the complexation strength. , Moreover, Borisova and Hancock only detected the 1:1 lanthanide complexes with such tetradentate mixed N- and O-donor ligands in solutions, while the 1:2 lanthanide complexes had been identified by crystallography. ,, Ogden and co-workers first detected the 1:2 complexes of Nd­(III) and Am­(III) with PhenDA in aqueous solution, and Makrlík even assumed the existence of the 1:3 complex to interpret the solvent extraction data . What’s more, none of the aforementioned studies analyzed the complexation and its changing trend along the lanthanide series from the thermodynamic origin.…”
Section: Introductionmentioning
confidence: 99%
“…The dependences of the logarithm of the europium and americium distribution ratios (log D) on the logarithm of the total concentration of the electroneutral Tetraisopropyl Regarding the results of our previous papers, 13,[16][17][18]26 the considered twophase water-HNO 3 -M 3+ (microamounts; M 3+ = Eu 3+ , Am 3+ )-nitrobenzene-L--H + Bsystems can be described by the set of reactions:…”
Section: Resultsmentioning
confidence: 91%
“…8 Complexation of trivalent lanthanides and actinides with several novel diglycolamide-functionalized calixarenes has been studied recently. [9][10][11] Besides, some of these functionalized calixarenes have been applied for the isolation of carrier-free 90 Y from 90 Sr. 12 The dicarbollylcobaltate anion 13 and some of its halogen derivatives have been employed often for the solvent extraction of various metal cations (e.g., Cs + , Sr 2+ , Ba 2+ , Eu 3+ and Am 3+ ) from aqueous solutions into a polar organic phase, both under laboratory conditions for theoretical or analytical purposes, [14][15][16][17][18] and on the technological scale for the separation of some high-activity isotopes in the reprocessing of spent nuclear fuel and acidic radioactive waste. 19,20 In this context we must state that the very bulky lipophilic dicarbollylcobaltate anion is present practically only in the equilibrium polar organic phase of the investigated two--phase extraction system 13 so that this univalent hydrophobic anion significantly facilitates the extraction of the mentioned cations from the aqueous phase into the organic one.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we chose to focus on phenanthroline carboxamide-based ligands because of their good extraction behavior as reported in the literature. Table lists some phenanthroline carboxamides that have already been studied. The dicarboxamide ligands have mainly been studied for the separation of actinides from the lanthanides and not as a direct application for adjacent lanthanides separation, although some data on some or the whole Ln series are often provided. In all of these studies, either a rather flat trend all along the series for N -dialkyl ligands or a preference towards light Ln for N -alkyl, N -aryl was obtained, and separation factors between minor actinides and lanthanides could reach up to 2 orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%